Comparative Analysis of Language Style Between Songs Lyrics of English and Indonesian Pop Singer - Emora Emda Putra; Hamzah Hamzah (Universitas Negeri Padang, 2021)
This study aims to compare the differences and the similarities between Indonesia and English pop song lyrics in the level of ideational metafunction, The systemic functional linguistics theory by Halliday was applied to analyze this research. The method used in this research was a descriptive research method. The results of the study show that they share two similarities and six differences in the level of ideational metafunction. The conclusion obtained from the findings is that they are more different rather than similar and the differences in how they produces the song lyric affected by the differences in cultural background of the song which are represented through song lyrics to the different ways of producing structure of clauses and selection of words in the ideational level of metafunction.